Epistemological aspects of computational simulations and their approach through educational simulations in high school. (February 2022) - Seoane, María Eugenia; Greca, Ileana M; Arriassecq, Irene
Computer simulations are currently used in diverse scientific disciplines as well as in science teaching. The simulations proposed for physics teaching are designed for specific purposes and allow studying natural phenomena through exploration and/or modeling. In this work, we present an analysis that, based on the theoretical frame provided by the nature of science (NOS), considers some aspects of present discussions on computer simulations that should be taken into account to promote scientifically literate citizens. We examine different types of simulations used, specifically, in the teaching of physics for high school in the past few years. We also explore some of the current philosophical thoughts on scientific simulations and which of their aspects could become part of the teaching–learning process when using simulations in science teaching—for example, the role of the model in simulations, the relationship between simulations and experimentation, the validity of knowledge resulting from simulations, and the role of animation in relation to the simulation used. Discussing these aspects from the viewpoint of the NOS would provide students with an updated vision of scientific activity so that they could analyze the information they receive daily and, as members of society, take a stand accordingly.